GARCH تفسير سلوك مؤشر سوق الأوراق المالية الليبي باستخدام نماذج - محمد الشركسي د.عادل; ناجي القبائلي أ.احمد (Scientific Journal of University of Benghazi, 2026)
This paper aims to predict the fluctuation movement of Libyan stock market (LSM) index by building a GARCH model of the daily returns during the period from April 2008 to July 2009. GARCH model was used because it takes into account the returns during the trading period as well as the volatility, which is a measure of the risk, and thus use this family of models to measure the relationship between returns and risk. The results of this study showed that the best model that explains the properties of LSM and can be used to predict is GARCH (1,1)